The Wiley-Blackwell handbook of infant development. Vol. 1 - Bremner, J. Gavin, 1949-; Wachs, Theodore D., 1941-; Wiley Online Library (Chichester, West Sussex : Wiley-Blackwell, 2010)
'Now in two volumes, the fully revised and updated second edition of The Wiley-Blackwell Handbook of Infant Development provides comprehensive coverage of the basic research and applied and policy issues relating to infant development. Updated, fully-revised and expanded, this two-volume set presents in-depth and cutting edge coverage of both basic and applied developmental issues during infancy. Features contributions by leading international researchers and practitioners in the field that reflect the most current theories and research findings. Includes editor commentary and analysis to synthesize the material and provide further insight. The most comprehensive work available in this dynamic and rapidly growing field.'--Provided by publisher.
Part II: Social cognition, communication, and language. -- Chapter 10: Emerging self-concept (Philippe Rochat, Emory University). -- Chapter 11: The Importance of Imitation for Theories of Social-Cognitive Development (Andrew N. Meltzoff, University of Washington, and Rebecca A. Williamson, Georgia State University). -- Chapter 12: Engaging Minds in the first year: The developing awareness of attention and intention (Vasudevi Reddy, Portsmouth University). -- Chapter 13: Preverbal communication (Andrew Lock, Massey University, and Patricia Zukow-Goldring, University of California, Los Angeles). -- Chapter 14: Early language (George Hollich, Purdue University). -- Part III: Social-emotional development. -- Chapter 15: Parent-infant interaction (Marc H. Bornstein, Eunice Kennedy Shriver National Institute of Child Health and Human Development, and Catherine S. Tamis-LeMonda, New York University). -- Chapter 16: Attachment in infancy (Germán Posada and Garene Kaloustian, Purdue University). -- Chapter 17: Early social cognitive skills at play in toddlers' peer interactions (Hildy Ross, University of Waterloo, Marcia Vickar, University of Waterloo, and Michal Perlman, University of Toronto). -- Chapter 18: Touch and physical contact during infancy: Discovering the richness of the forgotten sense (Dale M. Stack, Concordia University). -- Chapter 19: Emotion and its development in infancy (David C. Witherington, University of New Mexico, Joseph J. Campos, University of California, Berkeley, Jennifer A. Harriger, Cheryl Bryan, & Tessa E. Margett, University of New Mexico). -- Chapter 20: Temperament (Theodore D. Wachs, Purdue University, and John E. Bates, Indiana University Bloomington). -- Chapter 21: Culture and infancy (Charles M. Super and Sara Harkness, University of Connecticut).
Revised edition of: Blackwell handbook of infant development / edited by Gavin Bremner and Alan Fogel. 2001.
Includes bibliographical references and index.
Print version record; title from PDF of title page (Wiley Online Library, viewed Jan. 14, 2011).
Keywords: Infants -- Development -- Handbooks, manuals, etc; Infants -- Health and hygiene -- Handbooks, manuals, etc; Child development; Infant Care; Infant